Business Feasibility Analysis to Enhance the Competitiveness through a Business Development Strategy - Ghossa, Inez Shabrina; Handrito, Radityo Putro (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to analyze the business feasibility of Putri Jaya Motor Go Solution to improve competitiveness and develop a more structured business plan in response to increasing competition in the motorcycle spare parts market. Design/Methodology/Approach – The results indicate that the proposed service model is financially feasible, generating promising profits with relatively low risk. The implementation of digital-based services, particularly WhatsApp ordering and direct delivery, can help overcome promotional limitations, improve service differentiation, and enhance operational efficiency. Findings – This study provides practical insights into how small businesses in the motorcycle spare parts sector can adopt digital-based service innovations and customer-oriented strategies to strengthen competitiveness. The findings offer a business development reference for MSMEs seeking sustainable growth through technology utilization and improved service models. Originality/Value This research provides value by assessing the feasibility of an innovative WhatsApp-based ordering and delivery model, offering practical insights into how small repair and spare parts businesses can leverage technology to enhance service quality, efficiency, and long-term competitiveness.